PENGARUH BUDAYA PEMBELAJARAN ORGANISASI DAN EFIKASI DIRI TERHADAP KINERJA AKADEMIK MAHASISWA MELALUI MEDIASI MOTIVASI - Ajeng Hardianto, Alviana; Salsabilla Ardine Pranindy, Jihan; Tri Siwi Agustina, Tri (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This study investigates the impact of organizational learning culture and self-efficacy on students' academic performance, considering motivation as an important mediator. Using quantitative methods and a survey of students at Airlangga University, data were analyzed using Structural Equation Modeling techniques (SEM-PLS). The findings show that motivation has a significant positive impact on academic performance. Although organizational learning culture does not have a significant direct effect, self-efficacy proves to be a strong factor. Motivation emerges as an important mediator in the relationship between self-efficacy and students' academic performance. Limitations of this study include a sample limited to Airlangga University, which may not represent the entire student population, and a focus on a few factors without considering other potential variables. Based on these findings and limitations, further research with a larger and more diverse sample is recommended. Future studies can explore other factors influencing academic performance, such as learning environment, social support, and psychological elements. A deeper understanding of organizational learning and self-efficacy on academic performance can make a significant contribution to the educational literature.